Young Taiwanese Immigration To Argentina: The Challenges Of Adaptation, Self Identity And Returning - Trejos, Bernardo; Lan Hung , Nora Chiang (Penerbit Universiti Sains Malaysia (USM Press), 2012)
Research on Taiwanese migrants has primarily been conducted in Australia, New Zealand, the United States and Canada, but much less in non-English speaking countries such as Argentina. The literature on Taiwanese immigrants has also tended to overlook young people, whether born in Taiwan or in destination countries. The present research tries to fill in this gap by focusing on the family ties of young Taiwanese migrants in Argentina, and the role they play in their adaptation to Argentina and return-migration decisions. The objective of this research is to depict the situation of young people of Taiwanese origin in Argentina. The guiding question is, how do these young people view their family and national identity? The method of study is first a literature review mainly based on statistics, surveys and other secondary sources. Moreover, to get a snapshot of young return migrants from Argentina, 18 interviews with semistructured questionnaires were conducted in Taiwan between 2008 and 2009.